Identity and the Second Generation : How Children of Immigrants Find Their Space - Brettell, Caroline; Nibbs, Faith G. (Book collections on Project MUSE., 2016)
"This book explores the social worlds and spaces of experience of the children of immigrants. The driving question of the volume is: How do these young people construct an identity and a sense of belonging for themselves and how do they deal with processes of inclusion and exclusion?"--